Industrial training report: Wisma Tenaga Nasional Berhad (TNB) / Muhammad Faiz Salman Abdul Rahman - Abdul Rahman, Muhammad Faiz Salman (Universiti Teknologi MARA, Perlis, 2023)
Here at Wisma Tenaga Nasional Berhad (TNB) Kuantan, where this place is a complete game-changer to make myself exposed and ready in the industry phase, a 6-month pleasant experience that made a significant influence on me began. In order to prepare me for the realities of the working world in the future, the purpose of this industrial training report is to present what I have learned over the course of these 24 weeks and the technique I used to push myself outside of my comfort zone. Tenaga Nasional Berhad, also known as TNB, is the organisation I have chosen to help shape myself into a better version of myself in the coming period of work. TNB is broken down into a number of major departments, the most important of which are TNB Generation, TNB Transmission, TNB Distribution, and TNB Retail, which caters to end-user consumers. I receive training at Wisma Tenaga Nasional, namely at the Kuantan station, for the state of Pahang. For six months, I was assigned to the TNB Retail division. To guarantee that customers, whether residential, commercial, or industrial consumers, are satisfied with the service provided by TNB, this report also details the potential divisions and how work is allocated in the retail division of TNB. According to what I observed during my six months of training, TNB has a solid management structure that they treat seriously everyone participating in the organisation, regardless of their status. As a result, I cannot state that I found any weaknesses in this organisation. Even though I was unable to identify any vulnerabilities in this organisation, I was nevertheless able to discuss its strengths, weaknesses, opportunities, and dangers in my report. In addition to learning about working in an office environment, I was able to hone a variety of self-help abilities over this training time, including soft skills, communication with clients, data analysis skills, and mastery of new Excel skills. I'm also appreciative of having kind-hearted coworkers and knowledgeable supervisors to help me from the start of my training period till I graduate with a wealth of knowledge and abilities that I may put to use in the next stage of my life.